(untitled) (Research, Society and Development, 2023)
The food industry is constantly seeking to evolve, preparing foods that meet the needs of its consumers. On the other hand, consumers are prioritizing foods that have a good origin, a broad nutritional quality, and sensory quality. The aim is therefore to prioritize the reduction of both fat and sugar contents, being notorious in dairy products for these concerns for modifications, as it is a food that is easy to consume, and viable for all economic classes. In this sense, sensory analysis in favor of consumer acceptance concerning new product formulations leads to better visibility of its characteristics, thus verifying acceptance and purchase intention. Thus, the present study aims to evaluate the acceptance of natural yogurt sweetened with natural sweeteners, xylitol, and erythritol equivalent in sweetness to natural yogurt with 5.1% sucrose. The concentrations of xylitol and erythritol used for sweetening were 10.4% and 4.2%, respectively. There was no significant difference between the yogurts; there was only a difference between them when the attributes were evaluated separately. The attributes of flavor and sweetness were the decisive characteristics for choosing yogurt sweetened with xylitol over other yogurts sweetened with sucrose and erythritol.